Benteng Rotterdam Berdasarkan Kajian Perkembangan Benteng Kolonial Di Indonesia - Novida Abbas (Berkala Arkeologi, 2005)
Regarding the archaeological remains in the form of Fort Rotterdam in Makassar, there are still many things that can be revealed from this fort through specific archaeological studies with the help of Makassar historical sources. Archaeological studies that can be carried out on the remains of the fortress of Rotterdam include the art style of building the fort that was used at that time (XVII century) in Sulawesi, especially South Sulawesi, and what types of activities had occurred in the fort during its use. Thus, it is hoped that holistic data can be obtained about the ins and outs of the Rotterdam fort so that it can be used in its preservation efforts.